Answer:
Step-by-step explanation:
Its is a linear equation .that is to day a simple equation of a line whose values can be obtained through their intercept.intercept on x axis, y is zero and vice versa
Answer: The common ratio is -1/3
-----------------------------------------------------------
Work Shown:
Pick any term to divide it by the previous term. I'm going to pick the second term and divide it by the first term.
r = common ratio
r = (term 2) divided by (term 1)
r = (4/9) divided by (-4/3)
r = (4/9) * (-3/4)
r = (4*(-3))/(9*4)
r = -12/36
r = -1/3
The common ratio is -1/3
This means you multiply each term by -1/3 to get the next term
For instance
term 2 = r*(term 1)
term 2 = (-1/3)*(-4/3)
term 2 = ((-1)*(-4))/(3*3)
term 2 = 4/9
Answer:
Step-by-step explanation:
Yes sirrrskiiiii yessssss djfkdoelswlwpeoeososososodo
Answer:
He had origanlly had 68 altogether
Step-by-step explanation:
Because if u count the scrateched ones which was 6 is now 62 then add the other six because there was 12 and his brother scrateched half which is basically 12 / 2 = 6 so if u add the six is 68
What Im basically saying is 56 + 12 = 68